Usability Evaluation of Hospital Information System Applications Based on The System Usability Scale - Kurniadi, Arif; Wulandari, Fitra; Arinnisa , Halima (Procedia of Engineering and Life Science, 2024)
The key to successful technology adoption is to pay attention to several aspects including top management support, system quality, information quality, and user perception through usability. The Khanza Hospital Management Information System (SIMRS) application in the UDINUS Medical Records laboratory is prepared as a learning medium for students of the Medical Records and Health Information Study Program. This study aims to evaluate the use of Khanza SIMRS application based on user experience, namely students through usability testing to measure learnability, efficiency, memorability, error, and satisfaction.Quantitative research was designed through a survey to 3rd year students of D3 Medical Records and Health Information Study Program by purposive random sampling. Quantitative data was collected from 40 respondents by answering 10 questions of the System Usability Scale (SUS) questionnaire using a Linkert scale of answers Strongly Disagree, Disagree, Neutral, Agree, and Strongly Agree.The results showed SIMRS application with SUS Score 62 (0-100 scale), Acceptability Marginal Low, Grade D, and Adjective Rating category "OK". Recommendations for the SIMRS application in the learnability aspect need to add vertical navigation on the left screen for ease of eye-tracking, while in the memorability aspect, it is necessary to add tooltips, tour wizards, screen transitions, and prominent visual effects.